2017
DOI: 10.15446/ing.investig.v37n3.57957
|View full text |Cite
|
Sign up to set email alerts
|

Size optimization of shoulder filleted shafts with relief grooves for improving their fatigue life

Abstract: Although in scientific literature there are studies regarding the inclusion of relief grooves in order to diminish the amount of stress concentration in stepped shafts, the incorporation of optimization algorithms capable of parametrically determining their geometry remains unexplored. In this paper, an approach to the problem of size optimization of shoulder filleted shafts with relief grooves and subject to axial loads is presented. The objective of the optimization is to minimize the maximum value of stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Zeng clarified the optimal single-arc transition curve for sonotrodes with various cross-section ratios through finite element analysis [16]. Based on single-arc transition, González-Mendoza proposed that the design of a pressure relief groove can decrease the stress concentration [17]. Tu found that the effects of double-curvature arc transition, three-curvature arc transition, elliptical transition, and streamline transition on reducing stress concentration are superior to single-arc transition [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zeng clarified the optimal single-arc transition curve for sonotrodes with various cross-section ratios through finite element analysis [16]. Based on single-arc transition, González-Mendoza proposed that the design of a pressure relief groove can decrease the stress concentration [17]. Tu found that the effects of double-curvature arc transition, three-curvature arc transition, elliptical transition, and streamline transition on reducing stress concentration are superior to single-arc transition [18].…”
Section: Introductionmentioning
confidence: 99%
“…According to Relationship (17), a matrix between the force and displacement for the roller end can be derived. The expression for this is as follows:…”
mentioning
confidence: 99%
“…This study investigates the fatigue strength of hybrid buttwelded (BW) joints between a cast steel part and a UHSS plate, which have a crack-like defect in the weld root, parallel to the applied load direction and caused by permanent root backing. The studied hybrid BW joint has a significant difference in material thicknesses, and the axial misalignment may cause a considerable amount of secondary bending stresses in the welded joint [13]. The aim of this study is to investigate whether the fatigue capacity of joints can be enhanced by reducing stress concentration in the weld root through the implementation of a stress relief groove (SRG) design.…”
Section: Introductionmentioning
confidence: 99%
“…An optimization approach for stress reduction in stepped specimens subjected to axial loads is proposed in [1]. The purpose of optimization is to minimize the maximum value of stresses in the main shoulder fillet, thus increasing the fatigue limit.…”
Section: Introductionmentioning
confidence: 99%